2011
DOI: 10.1039/c1sc00430a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction anisotropy and shear instability of aspirin polymorphs established by nanoindentation

Abstract: Nanoindentation is applied to the two polymorphs of aspirin to examine and differentiate their interaction anisotropy and shear instability. Aspirin provides an excellent test system for the technique because: (i) polymorphs I and II exhibit structural similarity in two dimensions, thereby facilitating clear examination of the differences in mechanical response in relation to well-defined differences between the two crystal structures; (ii) single crystals of the metastable polymorph II have only recently beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
197
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(215 citation statements)
references
References 37 publications
15
197
1
2
Order By: Relevance
“…An F-d curve with pop-ins also implies a weak bond, i.e. the van der Waals interaction, between Se atoms of two different planes, along which the crystal can be easily cleaved (Varughese et al, 2011). These pop-ins are also attributed to homogeneous or heterogeneous nucleation of dislocations under the indenter tip (Varughese et al, 2013).…”
Section: Nanoindentation Analysismentioning
confidence: 99%
“…An F-d curve with pop-ins also implies a weak bond, i.e. the van der Waals interaction, between Se atoms of two different planes, along which the crystal can be easily cleaved (Varughese et al, 2011). These pop-ins are also attributed to homogeneous or heterogeneous nucleation of dislocations under the indenter tip (Varughese et al, 2013).…”
Section: Nanoindentation Analysismentioning
confidence: 99%
“…In addition to being easily controllable, the more stable polymorphic form also complies with requirements described in the Q6A Guide of the International Commission on Harmonization (ICH) for solid form selection (Grant et al, 2004). Kristl et al, 1996;Sohn et al, 2008;Lutker et al, 2011;Tutughamiarso et al, 2012) Acetylsalicylic Acid Analgesic IV 2 I (TSRL inc, 2012; Klein et al, 1994;Vishweshwar et al, 2005;Bond et al, 2011) Ibuprofen Analgesic II 2 I (TSRL inc, 2012;Shankland et al, 1996;Erk et al, 2004;Stone et al, 2009;Derollez et al, 2010) Acetaminophen Analgesic IV 6 I (TSRL inc, 2012;Haisa et al, 1974;Naumov et al, 1998;McGregor et al, 2002;Parkin et al, 2002;Peterson et al, 2002;Fabbiani et al, 2004 (Otsuka et al, 1983;Stephenson et al, 1998;Kennedy et al, 2003;Kasim et al, 2004;Aguiar et al, 2011) Ciprofloxacin Antibiotic III 3 II (hydrate) (TSRL inc, 2012;Turel et al, 2003;Fabbiani et al, 2008;Fabbiani et al, 2009;Fabbiani et al, 2011) Doxycycline Antibiotic IV 2 ‡ (TSRL inc, 2012; Legendre et al, 2012) Erythromycin Antibiotic IV 4 Dihydrate (TSRL inc, 2012;Fukumori et al, 1983;Stephenson et al, 1997;Miroshnyk et al, 2006) Sulfamethoxazole Antibiotic IV 4 III (hemihydrate) (TSRL inc, 2012;…”
Section: Bioequivalence and Bioavailabilitymentioning
confidence: 99%
“…It was only in 2005 that polymorphism was verified in this API, in which it was found that form II (metastable) coexists with form I (Vishweshwar et al, 2005). Subsequently, form II was isolated, and its conversion into form I occurs at room temperature, which is accelerated by mechanical grinding (Varughese et al, 2011).…”
Section: Acetylsalicylic Acidmentioning
confidence: 99%
“…In the crystal engineering context [13][14][15][16], this particular feature has been utilized in the recent past to establish structure-property correlations for a variety of molecular solids; one such aspect is in the study of intergrowth polymorphism in active pharmaceutical ingredients (APIs) such as aspirin [3] and felodipine [8]. The higher spatial resolution of the nanoindentation technique, vis-à-vis X-ray diffraction (XRD), is especially relevant in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation is a technique that can be employed to quantitatively measure the mechanical properties of relatively small volumes of materials [1][2][3][4][5][6][7][8][9][10][11][12]. In the crystal engineering context [13][14][15][16], this particular feature has been utilized in the recent past to establish structure-property correlations for a variety of molecular solids; one such aspect is in the study of intergrowth polymorphism in active pharmaceutical ingredients (APIs) such as aspirin [3] and felodipine [8].…”
Section: Introductionmentioning
confidence: 99%